Physiological Differences Between Seasonal Dimorphs of Agonoscena pistaciae (Hemiptera: Aphalaridae) Elicit Distinct Host Plant Responses, Informing Novel Pest Management Insights. Issue 5 (27th August 2022) - Homayoonzadeh, Mohammad; Michaud, J P; Esmaeily, Mojtaba; Talebi, Khalil; Allahyari, Hossein; Wright, Denis J
Abstract: We examined differences in the physiology and life history between dimorphs of the common pistachio psyllid, Agonoscena pistaciae (Burckhardt and Lauterer) (Hemiptera: Aphalaridae), and how they differ in elicitating host plant production of key metabolites and volatile compounds involved in the recruitment of herbivores and natural enemies. Summer morphs had higher activities of glutathione S-transferase, carboxylesterase, acetylcholinesterase, and cytochrome P450 monooxygenase, superoxide dismutase, catalase, peroxidase, phenoloxidase, and a higher total protein content compared to winter morphs, whereas the latter had higher amounts of lipid, carbohydrate, and glycogen. Winter morphs were heavier, with a higher chitin content and longer preoviposition period, but greater fecundity and longevity than summer morphs. A lower LC50 to thiamethoxam for winter morphs resulted in higher mortality following exposure to the recommended rate of this insecticide in a greenhouse trial. Feeding by winter morphs elicited more strongly the release of volatile compounds known to be attractive to other herbivores, whereas feeding by summer morphs elicited more strongly the release of volatiles implicated in the attraction of natural enemies. Feeding by psyllids increased the concentrations of nitrogenous compounds, carbohydrates, vitamins, and amino acids in plants, the winter morph eliciting larger changes and more improved host plant quality. We conclude that winter morphs are more vulnerable targets for chemical control in early spring, whereas management of summer morphs could rely more on conservation biological control.